Tradução, adaptação transcultural e validação semântica do questionário “Humanities Score” e análise do perfil de exposição de estudantes de medicina da Unifenas - BH às humanidades - Vieira, Ilse Seubert Coelho (2019)
Introduction: The humanities are associated with personal development, with stress and burnout reduction, as well as with the improvement of personal qualities in clinical practice. Thus, knowing how medical students react to the exposure to the humanities is necessary in order to develop educational interventions that involve the humanities, and that are effective in positively impacting on the life of medical students and future physicians. Therefore, tools for reliable quantification are indispensable to provide objective subsidies to support such educational actions. However, we found that there was no research tool in Brazilian Portuguese that would quantify the exposure of medical students to the humanities. Objectives: To do the translation, transcultural adaptation and semantic validation of the instrument "Humanities Score" to enable its use in Brazil and analyze the exposure profile to the humanities of medical students at UNIFENAS-BH. Methodology: Translation and back translation processes, review by researchers, pre-testing and verification of the psychometric properties of a foreign language questionnaire. Results: Pre-testing used samples of 31 students and the final questionnaire was administered to 237 medical students to evaluate the psychometric properties. After statistical analysis of the construct, its structure became an "Exposure Scale to the Humanities" (EEH) with two subscales (the actual exposure scale to the humanities and an opinion scale about the curricular inclusion of the humanities), both with five-option answers in a Likert scale format. Exposure frequency scale analysis showed satisfactory internal consistency with a Cronbach's alpha coefficient of 0.689. It was observed that the students’ rate of exposure to the humanities seems to decrease along the medical course; the variables being a female, doing volunteer work, religion and extracurricular activities are related to higher levels of exposure to the humanities and opinion about the importance of human sciences in the medical curriculum. Conclusion: The objectives of this research study have been achieved – we have now a scale in Brazilian Portuguese that can measure the exposure of medical students to the humanities, consequently establishing a correlation between the behavior (action) and attitude (intention) of the students regarding the importance they give to the humanities in the medical curriculum